2021
DOI: 10.1038/s12276-021-00706-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HSPA7 in human atherosclerotic plaques sponges miR-223 and promotes the proinflammatory vascular smooth muscle cell transition

Abstract: Although there are many genetic loci in noncoding regions associated with vascular disease, studies on long noncoding RNAs (lncRNAs) discovered from human plaques that affect atherosclerosis have been highly limited. We aimed to identify and functionally validate a lncRNA using human atherosclerotic plaques. Human aortic samples were obtained from patients who underwent aortic surgery, and tissues were classified according to atherosclerotic plaques. RNA was extracted and analyzed for differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Direct binding of lncRNA and miRNA appears to alter the cellular function of downstream molecules, leading to abnormalities of vascular endothelial cells and SMCs (39)(40)(41)(42). miR-188-3p was predicted to be targeted by RASSF8-AS1 based on bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Direct binding of lncRNA and miRNA appears to alter the cellular function of downstream molecules, leading to abnormalities of vascular endothelial cells and SMCs (39)(40)(41)(42). miR-188-3p was predicted to be targeted by RASSF8-AS1 based on bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although lncRNAs lack functional initiation codon and termination codons [184], some lncRNAs have been shown to translate into micropeptides [185]. In a study conducted by Ann et al [186], it was shown that among the 380 RNAs that differed in expression between plaque and control tissues, lncRNA HSPA7 was increased by oxidized low-density lipoprotein (oxLDL). HSPA7 knockdown decreased human aortic smooth muscle cell migration as well as IL-1 and IL-6 secretion and expression.…”
Section: Lncrna and Atherosclerosismentioning
confidence: 99%
“…( Yan et al, 2022 ) Besides MIR17HG also inhibits non-small cell lung cancer via functioning as a ceRNA of miR-142-3p. ( Wei et al, 2020 ) Through this regulatory mode, lncRNAs are widely involved in the course of various diseases, including thyroid cancer ( Guo et al, 2021 ), renal fibrosis ( Tang et al, 2021 ), atherosclerotic plaques ( Ann et al, 2021 ), among others.…”
Section: Function Of Lncrnasmentioning
confidence: 99%